Latin America Bets on Chinese Lessons - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2005)
These days, all roads in international trade seem to lead to China, even in the case of a small country like Chile, which recently signed a free-trade agreement with the Asian giant. It was China’s first free trade treaty with a Western country, and it opens new international routes for its products. In addition, Chinese authorities say the agreement will make Chile a bridge for investments from China into the rest of Latin America. This much is certain: Both China and the dynamic Southeast Asia region are the focal point for Latin American exports. However, the road to Asia is filled with cultural challenges and stereotypes that must be overcome in order to understand the business people and consumers in such a diverse geographical region. Latin American academics and other experts explain the keys to carrying out a successful approach to building businesses and developing human resources in Asia.